Science and society actions by our universities: From kindergarten to the President of the French Republic - Dole, Hervé (Septentrio Conference Series, 2023)
Watch VIDEO. What are the best practices of universities in terms of science and society activities? For what aims? How to go beyond dissemination and top-down approaches? How these strategies interplay with open science and citizen science strategies and actions of our universities? Science and society is defined here as all actions, methods, strategies deployed by universities to interact with the public, schools, inhabitants, policymakers, media, associations, businesses, and citizens at large – thus not only with academia and students. Science obviously encompasses all human, social, natural, experimental, exact and health sciences. I will present the results of a benchmark (we performed with Sorbonne Université and SIRIS academics) about international practices of universities to interact with the public. I will highlight some examples from Université Paris-Saclay, like outreach to various publics, from kindergarten (about general science) to the President of the French Republic and his government (about climate change by the IPCC), with an emphasis on schools and girls in STEM. A link with culture will also be made, as art and science is also an interesting way to touch a new public in a less formal way. This keynote, taking place during the World Science Day for Peace and Development, will also briefly mention complotism and fake news, still spreading quickly without obvious efficient ways to counteract them, although a partnership with some media can help.